Energy Evolution Characteristics and Performance Parameter Degradation of Rubber-Mixed Concrete in Sulfate Attack Environment - Xiu-ling Chen (Advances in Civil Engineering)
In order to study the sulfate resistance of rubber concrete (RC), the compressive strength test of RC with different contents (0%, 5%, 10%, and 15%) was carried out, and the proportion of RC with standard curing for 28 days was optimized. Sulfate attack test was carried out on the selected RC and compared with normal concrete (NC). The degradation degree was measured from the effective porosity, relative dynamic elastic modulus, SO42− concentration, and SEM microstructure observation after different attack times. The energy analysis method is used to study the evolution law of total strain energy, elastic strain energy, and dissipated strain energy of NC and RC in the process of deformation and failure after different attack times, and the influence of sulfate attack on concrete is explored from the perspective of energy. The results show that with the progress of sulfate attack, the effective porosity of NC and RC both decreases first and then increases, and the relative dynamic elastic modulus increases first and then decreases. Rubber is beneficial to improve the sulfate resistance of concrete, delay the attack of SO42− on concrete, and improve the ductile deformation of concrete. This study can provide a theoretical reference for the application of RC in practical engineering.